E-HRM: The Key to Modern Employee Performance with Productivity as the Mediator - Diaz Prasetia Darmawan; Chandra Fitra Arifianto (Pattimura University, 2026)
This study aims to analyze the impact of electronic human resource management (e-HRM) on employee performance, both directly and indirectly through the mediating role of work productivity. Using a quantitative approach and saturated sampling method, the data were analyzed using Structural Equation Modeling (SEM). The results show that e-HRM does not have a significant direct effect on employee performance, but it does have a significant effect on work productivity. In addition, work productivity significantly affects employee performance and effectively mediates the relationship between e-HRM and performance. These results indicate that the implementation of e-HRM does not automatically improve performance, but operates indirectly by encouraging increased work productivity. Theoretically, this study expands the understanding of the role of e-HRM by emphasizing the importance of productivity as a key mechanism for explaining the relationship between e-HRM systems and employee performance.